Impacto acadêmico do Núcleo Interdisciplinar de Suporte ao Estudante (NISE) do Centro de Tecnologia da Universidade Federal do Rio Grande do Norte no processo de inclusão - Araujo, Luiza Fernandes Freire Mariz de (2023)
This research initially emerged with the purpose of reflecting on the processes of inclusion of students with specific needs in the context of the Federal University of Rio Grande do Norte (UFRN). The growing number of students with specific needs entering the University has promoted strategic accessibility actions for these students in their university context. From this perspective, according to Martins (2019), accessibility centers contribute to improving the pedagogical conditions provided to students. Thus, the object of study of the research will be the Student Support Interdisciplinary Nucleus (NISE), which operates in the Technology Center (CT) of UFRN, which presents itself as a policy strategy for inclusion of the referred Center. With this, the general objective of the research is to analyze the impact of the actions of the Interdisciplinary Student Support Center (NISE in Portuguese) in the Technology Center of the Federal University of Rio Grande do Norte, in the process of university inclusion. To delimit the participants, a cut was made in the universe of students and teachers of the Technology Center based on the researcher's place of work, who develops her activities in the Department of Civil and Environmental Engineering. As data production instruments, semi-structured interviews were carried out with the public servants of the Accessibility Nucleus, the students attended by the NISE of the Civil and Environmental Engineering courses and with the professors who have students assisted by the Nucleus of the same courses of the Technology Center of the Federal University of Rio Grande do Norte. The methodology used in the research is exploratory and descriptive, with a qualitative approach. The interviews carried out were recorded and transcribed. In addition, legal documents that guided the creation of the NISE were consulted. This investigative movement helped us to understand the parameters and needs that are relevant in the formation process of the Nucleus. The next step, data analysis, was performed using categories established from the research objectives. With the completion of the research, it was possible to identify the relevant importance of the actions carried out by the NISE, promoting the inclusion of students with specific needs in the Technology Center and contributing to the qualification of the teacher's mediation with these students, thus providing academic accessibility. During the research, and based on its data and analyses, an Educational Product was built in the form of a handbook with pedagogical guidelines that can contribute to the teaching and learning of students with specific needs in higher education and that they, as far as possible, are based on the Universal Pedagogical Design (KRANZ, 2014)